KEBENARAN AGAMA DALAM FILSAFAT PERENNIAL: (Prespektif Seyyed Hossein Nasr) - Rusdin Rusdin (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri (UIN) Datokarama Palu, Indonesia, 2018)
Religion is a bond, a doctrine for humans for the sake of peace of life, while anxiety is a barren soul of truth. Someone who does not find his identity makes his life uncertain. In this context, Seyyed Hossein Nasr reveals that the truth of religion is demand, instructions with the using of perennial philosophy. Truth always perceives itself the best, eternity that never ends. Essence or authenticity is another form of the existence of God.The essence of religion is fitrah that is inseparable from God's truth as a source of truth. Authenticity is an essential truth, always connected with the Creator, religion must be sourced from the Enormous.